(untitled) (Global Journal of Science Frontier Research, 2014)
The research showed that butterflies are the main pollinators of Ixora coccinea in Nambor Wild Life Sanctuary, Assam. The family of Papilionidae (6 species), Pieridae (3 species) and Nymphalidae (2 species) are mainly found as insect visitors. The time of the day had a significant effect on the number of butterflies that visited the flowers. Afternoons had more visitors than mornings suggesting that the butterflies become active as the day warms up. The frequency of butterflies visited the flowers was high during 09:00-13.00 hour and month of april to august. Flower colour had a positive influence on the number of visitors. The flowering season of I.coccinea is mainly summer and butterflies are deriving most of their heat from the sun.